2013
DOI: 10.9734/ijpss/2013/4981
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Medicago sativa Yield under Deficit Irrigation Technique in Sandy Soil

Abstract: Deficit irrigation technique was introduced to find the best means to conserve irrigation water in arid lands. The most common model describing deficit irrigation is water yield response model. The main advantage of such model is that it can predict relative yield drop, which arises from relative water deficit, in order to maximize the economic return. The disadvantage of the model is that it uses evapotranspiration (ET), estimated by using meteorological data, which affects the applicability of the model when… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…The results of the study indicated that, the Penman model could be effectively utilized to calculate ET 0 using meteorological data. Moreover, Omran (2005 and2013) planned maize and clover irrigation scheduling. Soil water data were utilized in lieu of evapotranspiration.…”
Section: Overmentioning
confidence: 99%
“…The results of the study indicated that, the Penman model could be effectively utilized to calculate ET 0 using meteorological data. Moreover, Omran (2005 and2013) planned maize and clover irrigation scheduling. Soil water data were utilized in lieu of evapotranspiration.…”
Section: Overmentioning
confidence: 99%